Macrophages in periapical lesions: Potential roles and future directions - Song, Yao; Li, Xinying; Huang, Dingming; Song, Hongjie (Frontiers in Immunology, 2022)
Periapical lesions are microbe-mediated infectious diseases which occur in the apical region of affected teeth with swelling, pain, and possible systematic impacts. A complex interaction between exogenous bacteria with host immune system determines the development, the progression, and the outcome of periapical lesions. As consequence, without timely treatment for affected teeth, destructions of bone tissues, resorptions of roots and surrounding tissues, and the loss of teeth would severely worsen the living quality of patients and bring brilliant economic burdens to patients and medical organizations. Macrophages are a group of heterogenous cells which are able to play multiple functions in the development of microbe-mediated infections, the destruction and reconstruction of bone tissues, and the microbe-host interactions. However, the differential infiltration of polarized macrophages complicates the understanding of the regulatory mechanism affecting periapical lesion progression. Therefore, this review provides a comprehensive review of the current advances concerning the potential role of macrophages in determining the turnover of human periapical lesions. For one way, the differentiated state of macrophages might indicate the progressive or stable condition of lesions. For another way, the predominance of bacteria invasion could regulate the differentiation and function of macrophages involved in periapical lesion. In addition, alternative strategies for the treatment of apical periodontitis are discussed.